2013
DOI: 10.1093/database/bat034
|View full text |Cite
|
Sign up to set email alerts
|

lncRNome: a comprehensive knowledgebase of human long noncoding RNAs

Abstract: The advent of high-throughput genome scale technologies has enabled us to unravel a large amount of the previously unknown transcriptionally active regions of the genome. Recent genome-wide studies have provided annotations of a large repertoire of various classes of noncoding transcripts. Long noncoding RNAs (lncRNAs) form a major proportion of these novel annotated noncoding transcripts, and presently known to be involved in a number of functionally distinct biological processes. Over 18 000 transcripts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…Databases like lncRNAtor (Park et al 2014) and ncRNAimprint (Zhang et al 2010) store comprehensive information about lncRNAs. Furthermore, the PLncDB deals with the information related to plant lncRNAs (Jin et al 2013), and lncRNome database has similar information stored for human (Bhartiya et al 2013). The ncFANs web server is useful for functional annotation of lncRNAs (Liao et al 2011), whereas DIANA-LncBase hosts elaborated information for both predicted and experimentally verified miRNA-lncRNA interactions (Paraskevopoulou et al 2013).…”
Section: Lncrnas and Associated Databasesmentioning
confidence: 99%
“…Databases like lncRNAtor (Park et al 2014) and ncRNAimprint (Zhang et al 2010) store comprehensive information about lncRNAs. Furthermore, the PLncDB deals with the information related to plant lncRNAs (Jin et al 2013), and lncRNome database has similar information stored for human (Bhartiya et al 2013). The ncFANs web server is useful for functional annotation of lncRNAs (Liao et al 2011), whereas DIANA-LncBase hosts elaborated information for both predicted and experimentally verified miRNA-lncRNA interactions (Paraskevopoulou et al 2013).…”
Section: Lncrnas and Associated Databasesmentioning
confidence: 99%
“…Several databases have been developed to curate computationally predicted and experimentally veriied lncRNAs, such as LncRNAdb [194], GENCODE [137], lncRNAtor [7], lncRNome [195], NONCODE [135], lncRNAWiki [134], LncRNA2Function [143] and starBase v2.0 [196]. LncRNAdb was the irst lncRNA database [194] and its updated version (LncRNAdb v2.0) integrates lncRNAs reported in livestock species (catle, sheep, pig, horse and chicken) [131].…”
Section: Functional Inference Of Lncrnamentioning
confidence: 99%
“…A number of distinct examples of each of these interactions and their biological regulatory outcomes have been reviewed in the literature. 48,49 A number of recent papers also suggest that a subset of lncRNAs could interact with smaller RNAs, including miRNAs, and modulate their regulatory effect. 50,51 Our group has validated one such regulatory interaction between a conserved pair of miRNA and lncRNA in zebrafish.…”
Section: Biological Function and Disease Associationsmentioning
confidence: 99%
“…Recently, our group has analyzed functional elements in lncRNAs, characterized by experimental datasets of RNA-protein, RNA-RNA interaction sites, and small RNA processing sites. 49,54 Our analysis hints that the functional elements in lncRNA are characterized by a lower variation frequency, almost comparable to that of protein-coding genes, suggesting that a comparison of sequence divergence based on whole lncRNA transcripts may be misleading. Nevertheless, other studies have also identified a small number of lncRNAs with recognizable degrees of sequence conservation between vertebrates.…”
mentioning
confidence: 93%